A retrospective survey of the seroprevalence of severe fever with thrombocytopenia syndrome virus in wild animals in Japan. Issue 2 (29th November 2020) - Okada, Ayaka; Hotta, Akitoyo; Kimura, Masanobu; Park, Eun‐sil; Morikawa, Shigeru; Inoshima, Yasuo
Abstract: Severe fever with thrombocytopenia syndrome (SFTS) has a high fatality rate and is caused by SFTS virus (SFTSV). Currently, SFTS is endemic to some areas in western Japan, and wild animals are considered to play important roles in the circulation of SFTSV in the environment. Previous retrospective surveys using samples mainly obtained between 2006 and 2015 revealed serological evidence of SFTSV infection in wild animals; however, seroprevalence before 2006 remains unclear. In this study, we investigated the presence of anti‐SFTSV antibodies in a total of 521 serum samples from nine wild animal species collected from 11 prefectures in central and eastern Japan between 1980 and 2000. All samples yielded negative results for antibodies to SFTSV, suggesting that there had been few or no SFTSV infections before 2000 in the sampled areas. Abstract : In this study, we investigated the presence of anti‐SFTSV antibodies in a total of 521 serum samples from nine wild animal species collected from 11 prefectures in central and eastern Japan between 1980 and 2000. All samples yielded negative results for antibodies to SFTSV, suggesting that there had been few or no SFTSV infections before 2000 in the sampled areas.